REASONS THAT CAN BE A FACTOR IN INCREASING THE TRANSPORT AND LOGISTICS SYSTEM IN THE REPUBLIC OF UZBEKISTAN - Kuchkorova Mukhlisakhon (Лучшие интеллектуальные исследования, 2023)
National transport and export organizations, which are actively involved in international cargo operations, are the first to recognize the importance of cargo logistics and understand the importance of cargo logistics, multimodal and terminal systems, transport technologies, modern telecommunications. Large transport and shipping organizations in Uzbekistan in Chali create their own terminal systems, therefore it is necessary to create computer systems information systems that support the logistics of cargo transportation and logistics services. The implementation of the logistics concept is one of the main activities aimed at reducing the overall costs of the enterprise. The logistics activity is an integral part of production and includes an intermediate range of product areas (services). Logistics in macro-resources reflect the joint integration work of enterprises through the integration of different organizations. All activities and operations related to the connection must be planned, managed and coordinated.